Shifted labor market risks? The changing economic consequences of job loss in the United States and West Germany - Martin Ehlert (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
This article analyzes how institutional changes in the welfare state influence income mobility around job loss in the United States andWest Germany. Drawing both on an analysis of changes in provisions for the unemployed and on panel data from the Panel Study of Income Dynamics (PSID) and the German Socio-Economic panel (GSOEP), I demonstrate that the material well-being of American households hit by job loss has decreased substantially over time because of welfare state retrenchment, while unemployed German households have experienced only little deterioration of their economic well-being despite worsening labor market circumstances and institutional changes. The analysis also reveals that women in the United States are especially disadvantaged by job loss because, in their case, the withdrawal of the state has not been counteracted by an increase in influence on the part of the family.
Keywords: 330; Arbeitslosigkeit; Arbeitslosenversicherung; Reform; Lebensstandard; Vergleich; USA; Deutschland